Risk Analysis of Increase Efficiency The Sugar Production Process Using The FMEA Method: Analisa Resiko untuk Meningkatkan Efesiensi Proses Produksi Gula Menggunakan Metode FMEA - Fachrudin, Moch Fais; Cahyana, Atikha Sidhi (Universitas Muhammadiyah Sidoarjo, 2025)
PT P, a sugar manufacturing company, has a sugar factory located in the Sidoarjo area. SHS sugar and quality manufacturing company. Production problems often cause long production delays, therefore managing the production process is very important. Failure modes and effects analysis (FMEA) was used to determine possible failure modes of sugar production. In the test results, various kinds of problems were found: transportation, grinding, purification, evaporation, crystallization. There are 5 factors that cause production inefficiency, namely: human factors, word methods, environment, raw materials and machines used. This resulted in that when the sugar production process was not optimal at PT P, the FMEA method was used to minimize production constraints in order to achieve production targets. After observing using the FMEA method, a value of 480 was obtained in the milling process.